2019
DOI: 10.1016/j.annals.2019.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Framing the land of the Northern Lights

Abstract: The development of affinities between the production and consumption of people and place is crucial for tourism development. We trouble front and backstage distinctions to examine how destinations are framed and critically explore the power of the imaginary in shaping how individuals apprehend and in turn create social worlds. Combining critical discourse analysis with stakeholder interviews, we scrutinise an influential television travel documentary as an instrument of cultural pedagogy, which recycles, recre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The destination image generates a tourist's attachment to the destination, resulting in the tourist's loyalty to the destination. The establishment of icons and symbols can be based on urban architecture [48]; rural scenery [49]; international companies related to the location [50]; advertising [51]; animals and plants [52]; movies [53]; activities; communities [54]; cultural heritage [55]; and astronomy [56]. Almost all the literature clarifies the positive effects of destination images on destination loyalty.…”
Section: From the Perspective Of Tourists (Symbols Images And Place Attachment)mentioning
confidence: 99%
See 1 more Smart Citation
“…The destination image generates a tourist's attachment to the destination, resulting in the tourist's loyalty to the destination. The establishment of icons and symbols can be based on urban architecture [48]; rural scenery [49]; international companies related to the location [50]; advertising [51]; animals and plants [52]; movies [53]; activities; communities [54]; cultural heritage [55]; and astronomy [56]. Almost all the literature clarifies the positive effects of destination images on destination loyalty.…”
Section: From the Perspective Of Tourists (Symbols Images And Place Attachment)mentioning
confidence: 99%
“…[ [51][52][53]56] From the perspective of suppers Khodadadi (2019) [59] explored the challenges faced by Iran's tourism suppliers in formulating a successful brand strategy for Iran and concluded that tourism suppliers face two main challenges: (1) lack of effort and resources;…”
Section: Perspective Examples Studies Under This Perspectivementioning
confidence: 99%